Micro-morphological adaptations of the wing nodus to flight behaviour in four dragonfly species from the family Libellulidae (Odonata: Anisoptera). Issue 4 (July 2018) - Rajabi, H.; Stamm, K.; Appel, E.; Gorb, S.N.
Abstract: Adult dragonflies can be divided into two major groups, perchers and fliers, exhibiting notably different flight behaviour. Previous studies have yielded conflicting results regarding the link between the wing macro-morphology and flight style in these two groups. In this study, we present the first systematic investigation of the micro-morphological differences of wings of percher and flier dragonflies in four closely related species from the family Libellulidae. Our results suggest that the shape and material composition of wing microstructural components and, in particular, the nodus are adapted to facilitate the specific wing functioning in fliers and perchers. The findings further indicate a decreasing trend in the area proportion of the soft resilin-dominated cuticle in the nodus in the series of species from typical perchers to typical fliers. Such a reduction in the resilin proportion in the nodus of fliers is associated with an increase in the wing aspect ratio. The knot-shaped protrusion at the nodus of perchers, which becomes notably smaller in that of strong fliers, is likely to act as a mechanical stopper, avoiding large wing displacements. This study aims to develop a novel framework for future research on the relationship between wing morphology and flight behaviour in dragonflies. Highlights: The shape and material composition of the nodus in percher and flier dragonflies are adapted to their flight behaviour. The area proportion of the soft, resilin-dominated cuticle is found to decrease from typical perchers to typical fliers. The presence of a knot-shaped protrusion in the nodus of percher dragonflies is likely to avoid large wing displacements. We suggest a framework for future research on the relationship between wing morphology and flight behaviour in dragonflies.